Accurate Encoding and Decoding of Emotional Facial Expressions in Schizophrenia - Flack, William F.; Cavallaro, Lorraine A.; Laird, James D.; Miller, Daniel R. (Psychiatry (Washington, D.C.), 1997)
This is a study of the encoding and decoding of emotional facial expressions by people diagnosed as schizophrenic. The results of most previous investigations have shown that schizophrenics are worse than other psychiatric and normal comparison groups at adopting and recognizing facial expressions of emotion. This study is the first in which both abilities were tested within the same group of outpatient subjects. In contrast to earlier findings, the results of this study indicate that this group of schizophrenics was equally proficient, as compared with unipolar depressive and normal medical control subjects, in the encoding and decoding of facial expressions of anger, sadness, fear, happiness, disgust, and surprise. Encoding and decoding responses in all three groups were largely unrelated. Some of the potential explanatory factors for these unusual findings include the older age of this sample and the use of a rating procedure in the decoding task that is more similar to the nature of decoding decisions made in social situations than those typically used by other investigators. The general conclusion that schizophrenics are deficient relative to comparison groups in the encoding and decoding of emotional facial expressions is not supported by these results.